Transboundary Air Pollution in South Korea: An Analysis of Media Frames and Public Attitudes and Behavior - Shapiro, Matthew A.; Bolsen, Toby (East Asian community review (Online), 2018)
The lack of a coherent policy to address seasonal air pollution in Northeast Asia is partly due to the complexity of the issue—that it is both domestic and transboundary in nature—and partly due to media frames that emerge in response to seasonal fluctuations. To provide a better understanding of these factors as well as their potential impact on public opinion and behavior, this paper claims that the varying narratives conveyed in the Korean media have an impact on and provide a basis for assessing Koreans’ opinions about the problem of air pollution, both transboundary and domestically. Invoking the extant literature that connects media effects with public opinion about air pollution, the analysis proceeds in two stages. First, based on an analysis of Yonhap News Agency reporting, it is shown that the emerging media-based frames are dominated by China and health-related content. Second, and in light of these frames, a survey is conducted of a representative sample of Seoul Metropolitan Area residents to determine how attention to the air pollution issue drives attitudes and, in turn, how such attitudes may be associated with specific pollution-reduction actions. Consistent with the media-based frames, it is shown that one’s attentiveness to the air pollution issue increases the importance one places on reducing Korea’s air pollution. Knowledge about air pollution also decreases one’s satisfaction with both Korea’s and China’s air pollution-reduction efforts. Knowledge about air pollution does not impact on Koreans’ decision to minimize exposure to air pollution outdoors (by wearing masks) or indoors (by using air purifiers), but it does increase the likelihood that one will simply stay indoors, indicating that health concerns are paramount for the average citizen.